T-cell Cytokines in Pregnancy - PICCINNI, MARIE-PIERRE (American journal of reproductive immunology (1989), 2002)
PROBLEM: Immunological mechanisms induced by T cells may play an important role in preimplantation embryo development, in implantation process and in the phenomenon of fetal allograft tolerance. METHODS: We review existing data on the role of T cells in pregnancy. RESULTS: The production of LIF, interleukin (IL)‐4, IL‐10 and M‐CSF by the decidual T cells may contribute to the maintenance of pregnancy. T cells are not only confined to the uterus. T cells are also present in cumulus oophorus and are able to produce LIF and IL‐4. CONCLUSIONS: These findings may provide an initial cue in favor of the possibility that different cytokines produced by T cells acting in concert are required to create a suitable microenvironment for the preimplantation embryo development and for the maintenance of pregnancy. T cells could work in parallel with other cells present in the decidua and cumulus suggesting a complex network of hormones, cytokines and cells.